Busy boards and earnings management – an Australian perspective. Issue 3 (18th October 2019) - Tham, Yeut Hong; Sultana, Nigar; Singh, Harjinder; Taplin, Ross
Abstract : Purpose: The purpose of this paper is to assess whether multiple directorships have an influence on earnings management for Australian publicly listed firms. This paper attempts to determine whether boards with multiple directorships are effective monitors and are able to constrain earnings management activities. Design/methodology/approach: The study adopts resource dependency theory on the relationship between multiple directorships and the extent of earnings management. Data analysis is based on publicly listed firms on Australian Stock Exchange utilising SIRCA database with a final pooled sample of 1, 815 firm-year observations from 2008 to 2012. Findings: Using different measures of multiple directorships, it is found that firms having board of directors with multiple directorships exhibit lower levels of earnings management. The results validate the applicability of resource dependency theory on the relationship between multiple directorships and the extent of earnings management suggesting that directors with multiple board seats by sharing experiences, skills, information and other resources limit the extent of earnings management by firms. Evidence also suggests that earnings management behaviour is more pronounced in larger firms compared to smaller firms and as predicted, industry audit specialists restrain earnings management activities. Practical implications: This study introduces methodological enhancements to the literature as it measures the multiple directorships in a number of different ways. Firms may be encouraged to actively seek board members with diverse backgrounds, international exposure/experience and pertinent skill-sets with multiple board memberships. These benefits will assist firms to determine the optimal board composition that will enable it to function effectively. Originality/value: Empirical studies on the association between multiple directorships and earnings management in Australia are scarce and this paper provides an update of the effect of multiple directorships on earnings quality in Australia.